Pasta Pati Jagung Putih Waxy dan Non-Waxy yang Dimodifikasi Secara Oksidasi dan Asetilasi-Oksidasi - Nur Aini; Purwiyatno Hariyadi (Jurnal Ilmu Pertanian Indonesia, 2007)
Modification of corn starch will give different effects depending on the corn variety. Gel forming capacity increased with increase in concentration of the samples and least gel concentration was maximal in higher amylose starch. Initial pasting temperature of native starch reduced from following oxidation and acetylation. Among the samples, the highest pasting temperature was recorded in native and values for peak viscosity during heating. The modified starch has better stability than native starch and lower tendency for syneresis and improve the freeze thaw stability.Keywords: white corn starch, oxidation, acetylation-oxidation, corn variety